Geo-Congress 2022 : Soil Improvement, Geosynthetics, and Innovative Geomaterials. - Lemnitzer, Anne (Geotechnical Special Publications., 2022)
GSP 331 contains 66 peer-reviewed papers on geosynthetics, innovative geomaterials, and soil improvement techniques presented at Geo-Congress 2022, held in Charlotte, North Carolina, March 20-23, 2022.